The first de novo transcriptome of pepino (Solanum muricatum): assembly, comprehensive analysis and comparison with the closely related species S. caripense, potato and tomato - Herraiz, Francisco J. (BMC Genomics, 2016)
BACKGROUND: Solanum sect. Basarthrum is phylogenetically very close to potatoes (Solanum sect. Petota) and tomatoes (Solanum sect. Lycopersicon), two groups with great economic importance, and for which Solanum sect. Basarthrum represents a tertiary gene pool for breeding. This section includes the important regional cultigen, the pepino (Solanum muricatum), and several wild species. Among the wild species, S. caripense is prominent due to its major involvement in the origin of pepino and its wide geographical distribution. Despite the value of the pepino as an emerging crop, and the potential for gene transfer from both the pepino and S. caripense to potatoes and tomatoes, there has been virtually no genomic study of these species. RESULTS: Using Illumina HiSeq 2000, RNA-Seq was performed with a pool of three tissues (young leaf, flowers in pre-anthesis and mature fruits) from S. muricatum and S. caripense, generating almost 111,000,000 reads among the two species. A high quality de novo transcriptome was assembled from S. muricatum clean reads resulting in 75,832 unigenes with an average length of 704 bp. These unigenes were functionally annotated based on similarity of public databases. We used Blast2GO, to conduct an exhaustive study of the gene ontology, including GO terms, EC numbers and KEGG pathways. Pepino unigenes were compared to both potato and tomato genomes in order to determine their estimated relative position, and to infer gene prediction models. Candidate genes related to traits of interest in other Solanaceae were evaluated by presence or absence and compared with S. caripense transcripts. In addition, by studying five genes, the phylogeny of pepino and five other members of the family, Solanaceae, were studied. The comparison of S. caripense reads against S. muricatum assembled transcripts resulted in thousands of intra- and interspecific nucleotide-level variants. In addition, more than 1000 SSRs were identified in the pepino transcriptome. CONCLUSIONS: This study represents the first genomic resource for the pepino. We suggest that the data will be useful not only for improvement of the pepino, but also for potato and tomato breeding and gene transfer. The high quality of the transcriptome presented here also facilitates comparative studies in the genus Solanum. The accurate transcript annotation will enable us to figure out the gene function of particular traits of interest. The high number of markers (SSR and nucleotide-level variants) obtained will be useful for breeding programs, as well as studies of synteny, diversity evolution, and phylogeny. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-016-2656-8) contains supplementary material, which is available to authorized users.